PENGARUH PELATIHAN, LINGKUNGAN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. MNC SKYVISION TBK - Wulandari, Suci; Nawangsari, Lenny Christina (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2019)
The purpose of this research is to analyze the effects of job training, environment and job satisfaction on employee performance at PT. MNC Skyvision Tbk. The job training is measured by training plans, processes and impacts. The job environment is measured by environment atmospheres both physically and psychologically. And job satisfaction is measured by achievements, confession and progress. Meanwhile employee performance is measured by contextual and task performances. The research method is quantitative descriptive to explain the effects of job training, environment and job satisfaction as independent variables and employee performance as dependent variable by using mathematic approaches and statistical measures. The data collecting technique used by distributing questionnaires to 228 employees of sales department at PT. MNC Skyvision Tbk. The data analysis technique used is multiple regression analysis to test research hypothesis. The research results showed that job training, environment and job satisfaction have positive effects on employee performance of sales department at PT. MNC Skyvision Tbk., either partially or simultaneously. In this case, the higher qualities of job training, environment and job satisfaction then the higher quality of employee performance.